Beberapa Model Pencerapan Pengajaran-Pemelajaran: Huraian Konsep, Andaian-Andaian Teoretikal, Serta Masalah-Masalah Berbangkit - Mohamed, Shukery (Penerbit Universiti Sains Malaysia, 1994)
This article discusses some of the major current models of teaching supervision. They include collaborative supervision, developmental supervision, differentiated supervision and clinical supervision. The discussion focusses on basic concepts in supervision and the theoretical assumptions in support of the models. It reveals an underlying message to help teachers to be more skillful and effective or 'to grow in their profession'. Apparently these models reject the notion of 'looking for teachers' faults, to inspect or to enforce power over teachers'. However, in utilizing these models one has to be sensitive and aware of our education system and the realities of our schools. There are various constraints which should be taken into consideration and resolved. Hence, teacher trainers are expected to be somewhat innovative in order to help trainees to develop their potentials and subsequently become successful teachers.